Anti-proliferative and apoptosis induction effects of Anacardium occidentale L. and Morinda citrifolia L. shoot extracts on breast, liver, and colorectal cancer cells - Meli, Mohd Amir Asyraf (2017)
Anacardium occidentale or also known as cashew and Morinda citrifolia or also known as noni are popular traditional plants among Malaysian community. The shoots of these plants are commonly consumed raw or blanched as side dishes or ‘ulam’ during meal times. Aside from shoots, other parts of the plants are also consumed in traditional medicines for the prevention and treatment of various diseases. Most of the study was focused on the fruit part of the plant and some of the study that used the plant leaves extracted with different types of solvents. Besides, the selected types of cancer was chosen as these three cancers were on top ten of most common cancer among Malaysian and there is limited study of cashew and noni against these cancer types. As cancer is one of the most leading cause of death in Malaysia, this study was aimed to determine the anti-proliferative effects of cashew and noni shoots in various types of cancer cell lines. Both shoots of cashew and noni were obtained from Taman Herba, Universiti Putra Malaysia and the freeze-dried samples were extracted with 70 % (v/v) ethanol. The selected cancer cell lines were breast cancer (MDA-MB-231) cells, liver cancer (HepG2) cells and colorectal cancer (HT-29) cells. The cells were treated with extracts of cashew and noni shoots for cytotoxicity test using (3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide) (MTT) assay. The results showed that cashew shoot extract had IC50 of 81.10 μg/ml, 307.50 μg/ml and 272.60 μg/ml against MDA-MB-231, HepG2 and HT-29 cells, respectively. Noni shoot extract showed IC50 of 49.72 μg/ml, 307.5 μg/ml and 65.43 μg/ml against MDA-MB-231, HepG2 and HT-29 cells, respectively. The MTT result also showed that both of the extract had no sign of cytotoxicity towards normal mouse fibroblast (BALB/c 3T3) cells. The extracts that demonstrated the IC50 value below 100 μg/ml were selected for further determination of apoptosis response using acridine orange (AO)/ propidium iodide (PI) dual fluorescent assay. The selected cancer cell lines were treated with extracts of cashew and noni shoots for 24, 48, and 72 hours of incubations and stained with nuclear staining dye which is acridine orange and propidium iodide and observed using fluorescence microscope. The results showed typical sign of apoptosis such as chromatin condensation, nuclear fragmentation and cell blebbing were markedly induced in all treated-cancer cells with cashew and noni shoots extracts after 24, 48 and 72 hours in time-dependent manner. In addition, the selected cancer cell lines were further analyzed for the determination of cell cycle progression using propidium iodide dye and flow cytometer. The data was analyzed using one-way analysis of variance (ANOVA) with Tukey’s post hoc test. The breast cancer cells were treated with three different concentrations of cashew (40 μg/ml, 80 μg/ml, and 120 μg/ml) and noni extract (25 μg/ml, 50 μg/ml, and 75 μg/ml) for 72 hours of incubation. As for colorectal cancer cells were treated with noni extract (33 μg/ml, 65 μg/ml and 98 μg/ml) for 72 hours. The results from cell cycle analysis showed significant increase in subG0 phase indicating apoptosis and significant decrease in G0/G1 phase in a dose-dependent manner. The cashew and noni ethanolic shoots extracts possessed potential anti-cancer properties, thereby gas chromatography mass spectrometry (GCMS) were carried out to characterize the active compounds in both plants. It was found that cashew shoot extract are abundant with sitosterol, tannin, pyrogallol, and phenol. As for noni shoot extract, they contained acetic acid and ethriol. In summary, both of the extracts showed cytotoxicity towards selected cancer cells and have the potential to be the studied further to understand underlying mechanism of the cashew and noni extracts in cancer cell lines and possibility to be developed as nutraceutical or functional food products.